Observation of leaf-cutting ants foraging on wild mushrooms - Lechner, Bernardo Ernesto (2012)
This study reports on the observation of an unusual behavior in leaf-cutting ants: foraging on wild mushrooms. A colony of Acromyrmex lundi in Buenos Aires (Argentina) was observed intensively harvesting basidiomes (mushroom fructifications) of wild Agrocybe fungus developing on a tree bark. Another colony maintained for a month in laboratory conditions also accepted Agrocybe mushroom and incorporated the cut bits into the fungus garden in the same way as they do with leaves. We recorded these events confident that they open a new perspective on the study of the feeding habits of leaf-cutting ants as well as on the relationship between their fungus garden and other organisms.